2017
DOI: 10.1159/000477266
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Ferritin with Diabetes and Alcohol in Patients with Non-Viral Liver Disease-Related Hepatocellular Carcinoma

Abstract: Introduction: Non-alcoholic fatty liver disease is a leading cause for hepatocellular carcinoma (HCC) in Sri Lanka. Diabetes mellitus, alcohol abuse, and liver inflammation are known to increase the risk of HCC. The present study evaluates serum ferritin levels in a cohort of patients with non-viral HCC (nvHCC). Methodology: Consecutive patients with nvHCC presenting to the Colombo North Liver transplant Service, Ragama, from January 2012 to July 2013 were investigated. All were negative for hepatitis B and C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
0
12
1
Order By: Relevance
“…Although there were studies found that SF levels may not play a role in the identification and diagnosis of HCC (34,35), other studies have also shown that it may be a marker for monitoring chemotherapy response in patients with HCC (33). Facciorusso A et al also found that the prognosis of HCC patients with higher SF levels was poor (36).…”
Section: Discussionmentioning
confidence: 99%
“…Although there were studies found that SF levels may not play a role in the identification and diagnosis of HCC (34,35), other studies have also shown that it may be a marker for monitoring chemotherapy response in patients with HCC (33). Facciorusso A et al also found that the prognosis of HCC patients with higher SF levels was poor (36).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a possible tumor biomarker may be serum ferritin rather than iron. However, because there is no exact correlation between iron inside the liver and iron in the blood, it is difficult to clarify the pathological features of ferritin on the poor prognosis of non-viral HCC (nvHCC)[24]. Results of a cohort study of 93 patients with nvHCC, 62 of whom had alcohol abuse problems, showed an increase in ferritin level in non-diabetics[24].…”
Section: Mechanisms Of Etiologymentioning
confidence: 99%
“…However, because there is no exact correlation between iron inside the liver and iron in the blood, it is difficult to clarify the pathological features of ferritin on the poor prognosis of non-viral HCC (nvHCC)[24]. Results of a cohort study of 93 patients with nvHCC, 62 of whom had alcohol abuse problems, showed an increase in ferritin level in non-diabetics[24]. However, further research needs to be done to assess the correlation between the impacts of alcohol and ferritin on NAFLD[24].…”
Section: Mechanisms Of Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Carcinogenesis of HCC is multifactorial and includes previous infection with hepatitis B or C viruses (HBV, HCV), aflatoxin B or alcohol consumption resulting in liver cirrhosis (4). New cancer sometimes develops with no previous link to the abovementioned agents, sometimes non-alcoholic steatohepatitis in diabetic patients has been associated with liver cancer (5).…”
mentioning
confidence: 99%